Poetics of the contingent: some essays about teaching (Práxis Educativa, 2022)
This study discusses a set of educational investigations particularly dedicated to the issue of teaching and its related practices, in order to explore the ways in which these works operate from the encounter between the field of the arts and the philosophical thought of Gilles Deleuze and Félix Guattari. It proposes a privileged alliance with the researchers David Lapoujade and Anne Sauvagnargues, who, by discussing themes about the anomalous, aberrant and animal in Deleuzo-Guattarian thought, enable an intensive exploration of the ideas of art and creation.  It points to the transmutation movements of the arts and the establishment of inseparable relationships between life, art and teaching. It concludes by demarcating the presence of a poetic will as a necessary perceptive mode for these pieces of research, in order to throw teaching at the risk of experimenting with chance and the becomings of this indeterminacy.Keywords: Teaching. Poetics. Educational research.